Hydronyms of Ethnic Origin in the Körös River Area (Papers in Arts and Humanities, 2024)
The subject of my study is the presentation of hydronyms of ethnic origin from a morphological approach. By processing the river hydronyms of the Körös region, which covers an area of more than 27,000 square kilometers, we can get an overview of the name-creating activities of the population of the studied area. From the history of Hungarian hydronym research, I mention the main registers, databases, and processings that contain ethnonyms, presenting the chronological and sociological diversity and variety of the region.In the lexical–morphological structure of two-part hydronyms, the most common are the extensional name parts that express the peculiarity (e.g., size, shape, color, temperature, age, condition, smell, taste, speed, sound, ethnic name). The role of ethnic names in hydronyms is determinative in inferring the occurrence of certain ethnic elements. Since the name itself identifies, the function of a place name is then the distinction from the environment, the separation from it. This method is also valid in hydronymy. As a result of this, we find such place names as Csehi, Oroszi, Tóti, Olaszi, and hydronyms such as Beseny-ér, Bosnyák-patak, Cseh-ér, Czigányi csermely, Kun-ér, Orosz-ér, Rác-patak, etc.
Keywords: onomastics; hydronyms; ethnonyms; localization; denomination